Aplikasi Frontend untuk Meningkatkan Customer Experience dan Mendapatkan Data Customer Menggunakan Metode Scrum pada Studi Kasus Livera - Anthony, Farrel; Birowo, Sigit (Jurnal Informatika dan Bisnis, 2025)
The development of digital technology has had a significant impact on human life, including institutions, organizations, and business actors. Rapid technological advancement has become a crucial factor for businesses to remain competitive in an increasingly dynamic market. Livera is a company engaged in the health beverage industry, with a focus on weight loss products. Currently, Livera does not yet have an application to fulfill customer satisfaction after purchase. Therefore, this study aims to design a website-based application intended to improve customer satisfaction, where customers can consume products according to a predetermined schedule, and the website application can also facilitate administrators in inputting and automatically accessing data. Customer experience represents an evaluation of feelings that can be identified through the experiences perceived by customers. Customer experience can be one of the most important determining factors for customers. This research is conducted using the Scrum method. The Scrum activities include product backlog, sprint backlog, daily Scrum, sprint review, and sprint retrospective. The roles in Scrum consist of the product owner, Scrum master, and the development team. This study employs a qualitative research method and the Scrum framework for system development. Data collection techniques used include non-participant observation, unstructured interviews, and literature studies from books and academic journals that serve as references related to customer experience, website design, and the Scrum method.